Learning Mathematics with Western Sumatera-Based Learning Video to Improve The Numerical Literacy Skill of Students - Ari Limay Trisno Putra; Dertha Mukthar; Susi Novita (Universitas Negeri Semarang, 2022)
Indonesia's Demographic Bonus refers to the number of productive age population which is higher than the elderly population. Improving the quality of human resources must continue to be carried out to make human resources knowledgeable, cultured in attitude or character, and competitive. Adat Basandi Syara', Syara' Basandi Kitabullah (ABS-SBK) refers to the guidelines for social life in Minangkabau. West Sumatra has a diversity of cultures and customs. Mathematics is one of the sciences that is taught at all levels of education, from basic education to tertiary institutions as mandated by the curriculum. Therefore, mastering mathematics is important. The OECD from PISA makes mathematics a focused subject. In this program, students must apply and practice their physical skills to real-life math literacy skills. The results of the international assessment and ranking of mathematics show that Indonesia still has a lower ranking than other countries. To improve students' numeracy literacy skills, interesting learning is needed and can add insight into the culture that surrounds students. For this reason, this research is a descriptive study that reveals culture in West Sumatra which was studied with West Sumatran humanists and explores supporting theories to improve numerical mathematical literacy skills in learning mathematics. The results are useful for starting Research & Development in the form of instruments or media for learning mathematics to improve students' numerical literacy.